2004
DOI: 10.1007/s00299-004-0892-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of transgenic barley lines produced by particle bombardment and Agrobacterium-mediated techniques

Abstract: Two barley transformation systems, Agrobacterium-mediated and particle bombardment, were compared in terms of transformation efficiency, transgene copy number, expression, inheritance and physical structure of the transgenic loci using fluorescence in situ hybridisation (FISH). The efficiency of Agrobacterium-mediated transformation was double that obtained with particle bombardment. While 100% of the Agrobacterium-derived lines integrated between one and three copies of the transgene, 60% of the transgenic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(132 citation statements)
references
References 43 publications
11
118
2
1
Order By: Relevance
“…Barley differs from rice and Arabidopsis in having two CO-like genes (HvCO1 and HvCO2) of which the former is unusual in having lost key residues in a normally highly conserved zinc-finger domain (B-box 2) (Griffiths et al 2003). Characterization of the roles and interactions of the various CO and FT genes in barley is now feasible because of the increased understanding of the gene families and the availability of new resources for functional analysis, including efficient transformation methods (Travella et al 2005) and a TILLING population (Caldwell et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Barley differs from rice and Arabidopsis in having two CO-like genes (HvCO1 and HvCO2) of which the former is unusual in having lost key residues in a normally highly conserved zinc-finger domain (B-box 2) (Griffiths et al 2003). Characterization of the roles and interactions of the various CO and FT genes in barley is now feasible because of the increased understanding of the gene families and the availability of new resources for functional analysis, including efficient transformation methods (Travella et al 2005) and a TILLING population (Caldwell et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…One study comparing two different protoplast-based transformation techniques found that donor DNA underwent structural changes and concatemerisations in protoplasts transformed by a DNA coprecipitation technique, while donor DNA integrated by cocultivation of protoplasts with Agrobacterium was often unaltered (Czernilofsky et al 1986). Other studies comparing Agrobacterium-to biolistics-derived transgenic lines in cereals found transgene expression to be generally less stable in biolistics-derived lines (Dai et al 2001;Travella et al 2005) which were characterised as having more numerous, and mainly partial, transgene copies. These three studies imply that the specific treatment of donor DNA either prior to or during DNA uptake may affect the final integrity of the transgene DNA in situ, and thus its stability and expression to varying degrees in the subsequent transformant population.…”
Section: Discussionmentioning
confidence: 99%
“…According to Travella et al (2005) and Li et al (2007), genetic transformation via particle bombardment presents some disadvantages, such as unstable inheritance and expression of the transgene, besides the possible integration of a high number of copies of the transgene in the plant genome. The present work differed from those in many aspects, because although our transgenic line was obtained via particle bombardment, only two copies of the transgene were integrated (as a single locus) in the plant genome, and the transgene inheritance followed the Mendelian pattern, with apparently stable expression, in all the crosses with commercial cultivars.…”
Section: Resultsmentioning
confidence: 99%